Review on Research Progress and Application of Reinforced Soil. Issue 3 (April 2021) - Cui, Meng; Hu, Linna; Fu, Xiao; Liu, Hailin
Abstract: Reinforced soil structure is particularly popular in the field of construction engineering because of its remarkable social, economic and environmental benefits, and is one of the current research hotspots. As a new type of geotechnical structure, reinforced soil has its mechanical characteristic affected by various complex factors, such as the type of reinforced material, the length of the reinforced material, the spacing between the reinforcements, the water content, the drawing directions, the earthquake, the traffic load and so on. Based on studying papers and books, this paper expounds the structural strength characteristic, the interface characteristics and stability of reinforced soil from three aspects, which include basic theory, experimental research and numerical analysis, and the applications of reinforced soil structures in geotechnical engineering are listed. Finally, in view of the current research status and development trend of reinforced soil, the focus and direction that need further research in the future are put forward.